Ageing of HDPE geomembranes in jet fuel A-1. Issue 6 (1st December 2009) - Rowe, R.K.; Rimal, S.
Abstract : ABSTRACT: The latest findings regarding the ageing of high-density polyethylene (HDPE) geomembrane (GM) exposed to jet fuel are presented. Data from std-OIT and HP-OIT tests both indicate that some component(s) of the antioxidant package are readily leached into the jet fuel but once this component is removed the OIT values remain relatively stable for up to at least 4 years. The std-OIT depletion rates for the readily leachable component of the antioxidant package are estimated from the available data. Based on the jet fuel immersion test at 23°C the depletion time to reach the residual standard oxidative induction time (OIT) is 1.6 years for 1.5 mm thick conventional GM and 5.5 years for the 1.5 mm fluorinated GM. Thus fluorination had a significantly beneficial effect in terms of slowing antioxidant depletion. Arrhenius modelling based on data at three temperatures (23, 9 and −22°C) is used to predict std-OIT depletion times at a temperature (−1°C) applicable to containment of jet fuel spill at Brevoort Island in the Arctic. The estimated depletion time ranged from 14–24 years for 1.5 mm thick untreated GM, 22–33 years for 2 mm untreated GM, and 26–33 years for 1.5 mm fluorinated GM. For GMs with a similar composition, the OIT depletion rate decreased approximately with the square of GM thickness. At 23°C the depletion rate in the diffusion test was only about one-quarter of that in an immersion test. Tensile elongation at yield increased with time of immersion in jet fuel. Tensile yield properties and initial tear resistance of the GM were lower when the GM was wet with jet fuel than when dry. However, no significant change in dry initial tear resistance was observed. No significant change in crystallinity was observed in GM exposed to jet fuel. The immersion data suggest that the 1.5 mm f-HDPE GM liner used to containing the hydrocarbon spill on Brevoort Island is likely to perform well for a period well in excess of 25 years at the average field temperature (−1°C). Based on the findings from the diffusion tests with jet fuel on one side and water on the other (i.e. similar exposure conditions to that in the field), the time to antioxidant depletion is likely to about four times longer than when immersed in jet fuel and so the depletion time in the field under these conditions is projected to be in excess of 100 years. These tests will need to be run for a much longer period of time to allow a better estimate to be made of the depletion rate of remaining antioxidants and service life of GM exposed to jet fuel.